Genome-wide evolution and function analysis of ALOG gene family in cotton - Liu, Zhen; Shen, Siyu; Cui, Zhijuan; Wang, Tao; Li, Pengtao; Wei, Yangyang; Peng, Renhai (Frontiers in Genetics, 2025)
BackgroundThe ALOG (Arabidopsis thaliana LSH1 and Oryza sativa G1) gene family is a class of transcription factors present in various plants. To elucidate the roles of ALOG genes in cotton, we systematically investigated the ALOG gene family across four cotton species (Gossypium hirsutum, Gossypium barbadense, Gossypium arboreum and Gossypium raimondii).ResultsIn this study, a total of 43, 42, 23 and 27 ALOG genes were identified from G. hirsutum, G. barbadense, G. arboretum and G. raimondii, respectively. The results indicated that cotton ALOG gene duplications originated before the speciation of Gossypium species, whole genome duplication, segmental duplication and transposable elements all play important roles in its expansion. In addition, cotton ALOG genes had undergone purifying selection during the evolution. Cis-element analysis revealed that TATA-box and CAAT-box are the most abundant in the promoters of cotton ALOG genes. Transcriptome analysis showed that the expression of ALOG genes in specific tissue is significantly higher than that in other tissues.ConclusionThis study enhances our comprehension of cotton ALOG genes, and these findings lay the foundation for functional characterizations of ALOG gene family.